Worlds of welfare : understanding the changing geographies of social welfare provision - Pinch, Steven (Routledge, 1997)
Worlds of Welfare demonstrates how a geographical perspective is crucial to understanding the diversity of welfare reform and explores the future of the welfare state in multicultural societies.